Sustainable Marine Fisheries and Their Contribution to Food Security and Coastal Economic Development - Ahmad Fauzi; Nur Aisyah Rahman (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Sustainable marine fisheries play a critical role in ensuring global food security while simultaneously supporting the economic development of coastal communities. Overexploitation of marine resources, climate change, and ineffective governance have posed significant threats to fisheries sustainability, particularly in developing coastal regions. This study aims to examine the contribution of sustainable marine fisheries to food security and coastal economic development through a systematic literature-based and empirical assessment approach. A mixed-methods design was applied, combining secondary data analysis from international organizations and peer-reviewed journals with qualitative insights from coastal fisheries management practices. The findings indicate that sustainably managed marine fisheries significantly enhance protein availability, stabilize livelihoods, and promote inclusive economic growth in coastal areas. Furthermore, fisheries governance frameworks that integrate ecosystem-based management and social equity principles demonstrate higher resilience against environmental and economic shocks. The study concludes that sustainable marine fisheries are not only a food production system but also a strategic economic pillar for coastal development. Strengthening policy coherence, community participation, and adaptive management is essential to maximize the long-term contribution of marine fisheries to food security and coastal economies.